PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN BIOSKOP ABC GARUT - BANI, ALDI; MUHAEMIN ADNAN, HILMAN; YUSUF, RAMAYANI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research aims to analyze and determine the influence of service quality on consumer satisfaction at Cinema ABC Garut. The population used in this research was 98 consumers using purposive sampling techniques. This sampling technique involved 98 regular consumers of Cinema ABC Garut or people who had at least visited Cinema ABC Garut. The data collection technique is through distributing questionnaires using a Likert scale. This research's analytical method uses linear regression. Based on the results of hypothesis testing data analysis in this research, it shows that service quality influences consumer satisfaction.